Mongolian National (Khalkha) Wrestling’s Uniforms of the 16th century - Buyandelger, Batmunkh; Munguntuul , Enkhbat; Bat-Ochir , Ishjamts (The New Research of Tuva, 2025)
This article examines the history of Mongolian wrestling uniform, with a special focus on the 16th century, and its importance for understanding the history of this kind of sport from the ancient times to the present day. Judging from the wrestling uniforms which appear in the copy  of the wall painting of Erdene Zuu monastery known as ‘Abtai Sain Khan’, preserved in the National Museum of Mongolia, we can conclude that 16th century  wrestling uniforms of the are not only very similar to the their 13th century counterparts (found in Shaanxi), but have also survived as the national wrestling uniforms of Mongolia today. The modern Mongolian national wrestling uniform consists of malgai (hat), zodog (uniform covering the chest), shuudag (uniform similar to shorts), and gutal (boots). However, according to the picture, these elements were used in wrestling in the 16th century. In the present-day Mongolian national wrestling uniforms the part which differs most from its historic predecessors is the malgai, which is unique in that it is the first image that has never been depicted in Mongolian historical wrestling monuments. But the zodog, shuudag, and gutal have been handed down without much change. Our research on Mongolian wrestling uniforms is important for a more accurate understanding of the culture, history, and evolution of Mongolian ethnicity.
Keywords: Mongolian national wrestling; wrestling uniform; Mongolia; zodog shuudag